Mexico - Collazo, Julie Schwietert (Eyewitness travel guides., 2024)
"Get closer to Mexico with DK Eyewitness. Exploring jungle-clad Mesoamerican pyramids. Swimming in the crystal-clear waters of a cenote. Devouring freshly made and flavorful street food. There are so many things to see and do in Mexico. Whatever your dream trip involves, this DK Eyewitness travel guide is the perfect companion. Our updated guide brings Mexico to life, transporting you there like no other travel guide does with expert-led insights, trusted travel advice, detailed breakdowns of all the must-see sights, photographs on practically every page, and our hand-drawn illustrations, which take you inside the country's neighborhoods"--